Evaluasi Kapasitas Panel Dalam Sistem Elektrikal Gedung D Universitas PGRI Palembang - Yudi Irwansi; M.Saleh Al Amin; Farabi Syahlevi (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
One of the mostimportant things in abuilding isthe provision of good and safe Facilities with out neglecting the artisti caspect of the building. For this reason , a Good andreliable installation is needed to beable to serve the power consumption Of the building.There search objective was to evaluate thed is tribution of electric Power according to the 2000 puil standard in building D, PGRI Palembang University and to calculate the panel capacity in building D,PGRI Palembang university.There search method used is quantitative and qualitativ emethods and various existing sources.The conclusion is that the total power of the lampis 1,785watts,ACis25,750 watts,and the socketis 18,500 watts. The typ eofuse of The cable conductor use disinaccord ancew ith the criteria for it scurrent carrying capacity.Thecapacity of the panels in building D of the PGRI Palembang university is stillup to standard,because the power used do esnotexceed th existingpower.